2002
DOI: 10.1111/j.1740-8261.2002.tb01666.x
|View full text |Cite
|
Sign up to set email alerts
|

AN INFECTED HIP PROSTHESIS IN A DOG DIAGNOSED WITH A 99mTC‐CIPROFLOXACIN (INFECTON) SCAN

Abstract: This case report describes the use of the 99mTc-labeled radiopharmaceutical ciprofloxacin (Infecton) in a case of hip prosthesis loosening in a dog. Serial planar radiographs were not conclusive, and culture of the synovial fluid was negative. Antibiotic treatment did not result in improvement of the lameness. Scintigraphy was performed with 99-Tc-Infecton, a tracer claimed to be specific for infection. Antibiotic treatment was interrupted 6 weeks prior to the examination. Planar and tomographic images at 3 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…Controversial results were obtained using other animal models like rabbits, camelids, dogs or swines to evaluate the ability of 99m Tc-ciprofloxacin to localize the infectious site, in severe acute pancreatitis, prosthetic joint infections or other suspected infections [23–26]. …”
Section: Ciprofloxacinmentioning
confidence: 99%
See 1 more Smart Citation
“…Controversial results were obtained using other animal models like rabbits, camelids, dogs or swines to evaluate the ability of 99m Tc-ciprofloxacin to localize the infectious site, in severe acute pancreatitis, prosthetic joint infections or other suspected infections [23–26]. …”
Section: Ciprofloxacinmentioning
confidence: 99%
“…a.— S. aureus Right thighMuscleCarrageenan inflammationScintigraphyHigh sensitivity, low specificityAungurarat [19]1 hn. a.— S. aureus , P. aeruginosa Right thighMuscle1.751.8Turpentine oil, heat killed bacteriaPromising agentMirshojaei [22]1 h10 8 — S. aureus Right thighMuscle3.2Sterile salineScintigraphyPromising agentZhang [20]4 h4 × 10 10 — Staphylobacterin Left thighMuscle4.301:03Turpentine oilSensitive radiopharmaceutical, simple preparationBhardwaj [14]24 h10 7 — S. aureus Right thighMuscle3.51.1Turpentine oilScintigraphyStable, safe preparation, specificSarda [23]10 7 —MS S. aureus JointKneeSterile salineScintigraphyGood sensitivity but lack of specificity for knee prosthesisPeremans [26]JointKneeScintigraphyUseful for infected hip prosthesis diagnosisAlexander [25]…”
Section: Summary Of Systematic Analysis Of the Literaturementioning
confidence: 99%
“…64 In companion animal species, Pseudomonas spp infections often involve the skin, urinary system, and ears, [65][66][67] along with SSIs and invasive device infections. 68,69 Biofilm formation by Pseudomonas spp can further complicate treatment. Identification of within hospital clusters of Pseudomonas infections should prompt investigation of potentially contaminated environmental, equipment (eg, endoscope), or consumable (eg, catheter preparation supplies) sources.…”
Section: Pseudomonas Sppmentioning
confidence: 99%
“…Animal study performed by Sarda et al [7] showed that infecton imaging has a good sensitivity in rabbits with infected knee prosthesis, but lack of specificity for the detection of S. aureus infection. Another study result indicated that infecton might be used in imaging a prosthetic hip infection in a dog [29]. Moreover, radiolabeled infecton has been shown to be useful for early diagnosis for osteomyelitis in rabbit by Southwood et al [30].…”
Section: Introductionmentioning
confidence: 97%